The effect of sets and repetitions of the spirometer by flow in cardiorespiratory parameters - Martinelli, Bruno (2017)
Introduction: The incentive spirometer helps pulmonary ventilation and the cardiorespiratory changes of its use are controversial. Objective: To evaluate the effect of sets and repetitions on cardiorespiratory parameters using a spirometer alinear flow (SAF). Materials and methods: The sample group consisted of 50 young people, healthy and sedentary. The evaluated parameters were: systolic blood pressure (SBP), diastolic (DBP), heart rate (HR), respiratory rate (RR), oxygen saturation (SaO2), minute volume (VE), tidal volume (VT), vital capacity (VC), maximal inspiratory pressure (Pimax), maximal expiratory pressure (Pemax), and peak expiratory flow (PEF). The moments of study were: initial evaluations (M1); 3 sets of 10 repetitions using SAF (M2); 3 sets of 15 repetitions using SAF (M3); and final evaluation (M4). Statistical analysis was made by t test, ANOVA and Tukey test (p < 0.05). Results: SBP and HR decreased in M2 after the 2[sup]nd[/sup] set. In the 3rd set, SBP and RR decreased. Comparing the initial and final variables in M2, SBP and RR decreased, and Pemax increased. After 1[sup]st[/sup] set in M3, SBP and SaO2 decreased. The 2[sup]nd[/sup] set: SBP, HR, RR, and SaO2 decreased. After the 3[sup]rd[/sup] set: SBP, HR, SaO[sub]2[/sub], and RR decreased. Comparing the initial and final variables in M3, SBP, HR, RR decreased, and Pi[sub]max[/sub] and Pemax increased. Comparing M4 to M1, Pi[sub]max[/sub], Pe[sub]max[/sub], and VC increased, and RR decreased. Conclusion: There are changes in cardiorespiratory parameters after the use of a spirometer alinear flow, especially in the sets with more repetitions.